A Study of Attitudes Towards Learning Biochemistry of Nursing Students in the Private Universities in the Eastern of Thailand - Sakdarat, Santi (Journal of Education Rajabhat Maha Sarakham University, 2025)
The objectives of this research were to analyze the attitudes of nursing students toward learning Biochemistry and compare these attitudes based on demographic factors, including gender, parents’ occupation, place of residence, cumulative GPA, and parents’ income. Additionally, the study investigates the relationship between students’ attitudes toward learning Biochemistry and their academic performance as well as their family’s economic background. The research sample comprised 165 nursing students enrolled in Biochemistry during the second semester of the 2024 academic year. The research instrument is questionnaire, assessing toure key included: 1) Attitudes toward Biochemistry knowledge, 2) Attitudes toward Biochemistry learning experience, 3) Attitudes toward Biochemistry in terms of behavioral tendencies, and 4) Attitudes toward Biochemistry concerning teacher efficiency. The data were analyzed using descriptive statistics, including mean and standard deviation, as well as inferential statistical methods such as the independent t-test, one-way ANOVA, and Pearson’s correlation coefficient. The findings indicate that students’ overall attitudes toward learning Biochemistry were at a moderate level (x̅=4.19, S.D.=.58). The highest-rated aspect was teacher efficiency (x̅=4.19, S.D.=.57), whereas the lowest-rated aspect pertained to behavioral tendencies (x̅=4.19, S.D.=.62). Statistically significant differences were observed in attitudes based on gender and place of residence. Furthermore, a negative correlation was found between attitudes toward Biochemistry knowledge and parents’ income, suggesting that students from higher-income families tend to have less favorable attitudes toward Biochemistry compared to those from lower-income backgrounds.